Corporate Governance, Leverage, dan Integritas Laporan Keuangan pada Perusahaan Badan Usaha Milik Negara - Putri Ayu Nurhalizah; Lia Uzliawati; Roza Mulyadi (Jurnal Akuntansi, 2023)
This study aims to determine the effect of Corporate Governance which is proxied by independent commissioners and audit committees, leverage on the integrity of financial statements. The population of this study is state-owned companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample selection method used was purposive sampling and 12 companies were selected with a total sample of 60 research data. The analysis technique used is multiple linear regression with SPSS version 25 software. The results show that independent commissioners and audit committees have no effect on the integrity of financial statements, while leverage has a negative effect on the integrity of financial statements.Keywords: Independent Commissioners, Audit Committees, Leverage, Integrity of Financial Statements